2016
DOI: 10.1007/s11468-016-0299-x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical T Circuit Modeling of Graphene-Based Metamaterial Broadband Absorber

Abstract: We demonstrate a broadband light absorber with its absorption being able to reach as high as 90 % and above ranging from the ultraviolet to the visible regimes. A theoretical model is given for the purpose of analyzing the physical mechanism of the absorption. By applying the equivalent T circuit model of metamaterial layers to the analysis of our designed absorber, our calculated results are in good agreement to that of the theoretical model and satisfy the perfectabsorption condition very well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…To overcome this problem, various physical mechanisms [ 18 43 ] to enhance absorption of graphene in the visible region have been proposed, which include strong photon localization on the defect layer in one-dimensional (1D) photonic crystals [ 18 , 28 , 33 , 38 ], total internal reflection [ 19 , 20 , 23 , 27 ], surface plasmon resonances [ 21 , 22 , 30 , 31 , 33 ], evanescent diffraction orders of the arrays of metal nanoparticles [ 34 ], and critical coupling to guided mode resonances [ 25 , 26 , 32 , 34 , 35 , 37 , 39 41 ]. Besides the absorption enhancement in graphene, achieving multiband and broadband light absorption in graphene is also important for some graphene-based optoelectronic devices from a practical point of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, various physical mechanisms [ 18 43 ] to enhance absorption of graphene in the visible region have been proposed, which include strong photon localization on the defect layer in one-dimensional (1D) photonic crystals [ 18 , 28 , 33 , 38 ], total internal reflection [ 19 , 20 , 23 , 27 ], surface plasmon resonances [ 21 , 22 , 30 , 31 , 33 ], evanescent diffraction orders of the arrays of metal nanoparticles [ 34 ], and critical coupling to guided mode resonances [ 25 , 26 , 32 , 34 , 35 , 37 , 39 41 ]. Besides the absorption enhancement in graphene, achieving multiband and broadband light absorption in graphene is also important for some graphene-based optoelectronic devices from a practical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…But, it is still a challenge, as pointed out in the very recent reports [ 44 46 ]. At present, different approaches have been proposed to broaden the bandwidth of graphene absorption in wide frequency range from THz [ 44 62 ] and infrared [ 63 65 ] to optical frequencies [ 19 , 23 , 29 , 31 , 34 36 , 38 40 , 43 ]. Especially, a multi-resonator approach was proven to be a very effective method to resolve the bandwidth limitation of graphene absorption in the THz and infrared regions [ 45 , 46 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the other horizon, owing to its exceptional electrical, electronics and optical properties, such as strong thermal power, wide carrier mobility, and extremely young module [56], have acquired considerable attention in the domain of the thin and lightweight metamaterial research. Graphene is a 2-dimensional, radioactive medium that offers electrical and optical control across a large spectrum of frequencies, such as THz [57][58][59] and GHz [60]. The graphene's conductivity can be managed by various parameters such as temperature, duration, dispersion rate, and chemical potential [58].…”
Section: Graphene-based Metamaterialsmentioning
confidence: 99%
“… 12 demonstrated that the overall dimensions of MA can be designed to offer perfect absorption at microwave frequencies owing to the matched impedance to free space. Since then, lots of devices 13 16 have been proposed and studied from the microwave 17 to terahertz 18 regions in order to obtain perfect absorption 19 , polarization-insensitive 20 , wide angle 21 and tunability 22 . The single-band high absorption is unsuitable in practical applications 23 .…”
Section: Introductionmentioning
confidence: 99%